Computational and experimental investigation of the strain rate sensitivity of small punch testing of the high-entropy alloy CoCrFeMnNi - Sean John (Journal of Alloys and Compounds, 2023)
The suitability of determining the strain rate sensitivity (SRS) of the CoCrFeMnNi high-entropy alloy (HEA) by small punch (SP) testing has been assessed at displacement rates ranging from 0.2 to 2 mm∙min-1. The stress was found to increase as the displacement rate was raised from 0.2 to 2 mm∙min-1, whereas the plastic strain distributions were similar in all cases. However, for a higher displacement rate of 10 mm∙min-1, the sample was found to exhibit a drop in strength and ductility attributed to casting defects. The strain-rate sensitivity exponent (m) was found to be 0.1387 whilst the Finite Element Analysis (FEA) simulations predicted a slightly smaller value of 0.1313. This latter value is closer to m = 0.091 obtained from nanoindentation strain rate jump tests since the results are insensitive to the presence of small casting defects. The relationship between the experimental and the empirically derived predicted properties from the SP tests revealed a high level of agreement for maximum stress properties. The properties predicted at 2 mm∙min-1 (R2 = 0.96) offered a stronger fit than at 0.5 mm∙min-1 (R2 = 0.92).